Method for producing resin particle dispersion liquid and method for producing electrostatic latent image developing toner

By controlling the acid value, carboxyl density, particle size and melt viscosity of the resin particles, combined with the amount of alkaline compounds with a specific neutralization rate, the problem of inappropriate electrostatic repulsion of resin particles is solved, shortening the time for manufacturing toners and improving Its morphology and viscosity stability.

CN119176953APending Publication Date: 2024-12-24FUJIFILM BUSINESS INNOVATION CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410707327.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-06-22
Filing Date
2024-06-03
Publication Date
2024-12-24

AI Technical Summary

Technical Problem

In the prior art, when manufacturing resin particle dispersion liquid, the acid value and carboxyl density range of the resin are too wide, resulting in inappropriate electrostatic repulsion of resin particles, affecting the aggregation time and the morphological control of toner, and the particle size and melt viscosity of resin particles. It is not within the appropriate range and the time for manufacturing the toner is extended.

Method used

By controlling the acid value of the resin in the range of 5 mgKOH/g to 30 mgKOH/g, the carboxyl group density is in the range of 1.0×10-7 mol/m2 to 3.0×10-6 mol/m2, the volume average particle size is 50nm to 300nm, and the particle size distribution index is GSDv is in the range of 1.18 to 1.99, and the melt viscosity at 105°C and the shear speed is 2.6s-1 in the range of 5000 Pa·s to 20000 Pa·s, using the amount of alkaline compounds based on the specific neutralization rate. , a suitable resin particle dispersion liquid is formed.

Benefits of technology

The time required to manufacture the toner is shortened, the uniformity of the particle size distribution and viscosity stability of the toner are improved, the environmental load is reduced, and the morphological control of the toner is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004873007910000221
    Figure BDA0004873007910000221
Patent Text Reader

Abstract

A method for producing a resin particle dispersion and a method for producing an electrostatic latent image developing toner, the method comprising a step of emulsifying a resin to form resin particles, the acid value of the resin being 5 mgKOH / g or more and 30 mgKOH / g or less, and the acid value of the resin being 0.5 mgKOH / g or less and the acid value of the resin being 0.5 mgKOH / g or less and the acid value of the resin being 0.5 mgKOH / g or less and the acid value of the resin being 0.5 mgKOH / g or less. The surface carboxyl group density of the resin particles is 1.0 * 10 <-7 > mol / m2 or more and 3.0 * 10 <-6 > mol / m2 or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for producing a resin particle dispersion and a method for producing a toner for developing an electrostatic latent image. Background Art

[0002] Patent document 1 discloses a method for producing crystalline resin particles by phase inversion emulsification, which comprises the following steps: (a) dissolving a crystalline resin containing an acid value in a mixture of at least two solvents, a first amount of a base and water to form an emulsion; (b) adding a second amount of a base to obtain a neutralization rate of about 100% to about 200%; and (c) converting the emulsion of step (b) into latex particles having a size of about less than 200 nm by adding water.

[0003] Patent document 2 discloses a resin for a toner, which comprises a polyester resin (A) containing a linear polyester (A1) and a nonlinear polyester (A2), wherein the acid value of (A1) is 50 to 200 mgKOH / g, and the glass transition temperature Tg (°C) and the flow softening point Tm (°C) of (A1) satisfy the relationship of Tm-Tg≤38.

[0004] Patent document 3 discloses a method for manufacturing a toner, which includes: a mixing step, in which a mixed dispersion containing resin particles and colorant particles is obtained by mixing an aqueous dispersion containing resin particles having an acidic polar group and an aqueous dispersion containing colorant particles containing a colorant; an agglomeration step, in which a coagulant containing divalent or higher metal ions is added to the mixed dispersion to agglomerate the resin particles and the colorant particles to form agglomerated particles; and a melting step, in which a chelating agent is added to the dispersion of agglomerated particles obtained in the agglomeration step, a monovalent water-soluble metal salt is added, and the mixture is heated to above the glass transition point of the resin to melt the resin particles and the colorant particles in the agglomerated particles.

[0005] Patent document 4 discloses a method for producing a resin particle dispersion, which includes the following steps: preparing a phase-transition emulsion obtained by phase-transition emulsification of a resin using a neutralizer, an organic solvent and an aqueous medium; and removing the organic solvent from the phase-transition emulsion, wherein the acid value A of the resin is greater than 8 mgKOH / g and less than 20 mgKOH / g, the neutralization rate of the resin based on the neutralizer is greater than 60% and less than 150%, and the organic solvent includes one or more organic solvents B selected from the group consisting of esters and ketones and one or more organic solvents C selected from alcohols.

[0006] Patent Document 1: Japanese Patent Application Publication No. 2016-210969

[0007] Patent Document 2: Japanese Patent Application Publication No. 2008-122931

[0008] Patent Document 3: Japanese Patent Application Publication No. 2013-109341

[0009] Patent Document 4: Japanese Patent Application Publication No. 2022-151290 Summary of the invention

[0010] The present invention aims to provide a method for producing a resin particle dispersion, wherein the resin particle dispersion is a resin particle dispersion for producing a toner, and the acid value of the resin is less than 5 mgKOH / g or exceeds 30 mgKOH / g, or the carboxyl group density on the surface of the resin particles is less than 1.0×10 -7 mol / m 2 or more than 3.0×10 -6 mol / m 2 Compared with the case of using a conventional method, the time required to produce the toner can be shortened.

[0011] Specific means for solving the above-mentioned problems include the following aspects.

[0012] <1>

[0013] A method for producing a resin particle dispersion, comprising the step of emulsifying a resin to form resin particles, wherein:

[0014] The acid value of the resin is 5 mgKOH / g or more and 30 mgKOH / g or less,

[0015] The carboxyl density on the surface of the resin particles is 1.0×10 -7 mol / m 2 Above and 3.0×10 -6 mol / m 2 the following.

[0016] <2>

[0017] The method for producing a resin particle dispersion according to <1>, wherein

[0018] The resin includes a polyester resin.

[0019] <3>

[0020] The method for producing a resin particle dispersion according to <1> or <2>, wherein

[0021] The resin particles have a volume average particle diameter of 50 nm or more and 300 nm or less, and a volume particle size distribution index GSDv of 1.18 or more and 1.99 or less.

[0022] <4>

[0023] The method for producing a resin particle dispersion according to any one of <1> to <3>, wherein

[0024] At a temperature of 105°C and a shear rate of 2.6s -1 The melt viscosity of the resin particles is 5000 Pa·s or more and 20000 Pa·s or less.

[0025] <5>

[0026] The method for producing a resin particle dispersion according to any one of <1> to <4>, comprising the steps of: using a basic compound in an amount such that a neutralization rate based on the following formula (1) is 30% or more and 80% or less,

[0027] Formula (1): Neutralization rate (%) = mb × n × 56.1 ÷ Mwb ÷ AV × 1000,

[0028] mb is the usage amount (g) of the basic compound per 1g of the resin,

[0029] n is the valence of the basic compound,

[0030] Mwb is the molecular weight of the basic compound,

[0031] AV is the acid value of the resin (mgKOH / g).

[0032] <6>

[0033] A method for producing a toner for electrostatic latent image development comprises the following steps:

[0034] A resin particle dispersion is obtained by the method for producing a resin particle dispersion according to any one of <1> to <5>;

[0035] aggregating the resin particles contained in the resin particle dispersion to form aggregated particles in a dispersion containing the resin particles; and

[0036] The dispersion liquid containing the aggregated particles is heated to fuse the aggregated particles into a body, thereby forming toner particles.

[0037] Effects of the Invention

[0038] According to <1> or <2>, the acid value of the resin is less than 5 mgKOH / g or exceeds 30 mgKOH / g, or the carboxyl group density on the surface of the resin particles is less than 1.0×10 -7 mol / m 2 or more than 3.0×10 -6 mol / m 2Provided is a method for producing a resin particle dispersion liquid which is used for producing a toner and which can shorten the time required for producing a toner, as compared with the case of the present invention.

[0039] According to <3>, a method for producing a resin particle dispersion for use in producing a toner and capable of shortening the time required for producing a toner is provided, compared with the case where the volume average particle size of the resin particles is less than 50 nm or exceeds 300 nm, or the volume particle size distribution index GSDv of the resin particles is less than 1.18 or exceeds 1.99.

[0040] According to <4>, at a temperature of 105°C and a shear rate of 2.6s -1 Provided is a method for producing a resin particle dispersion liquid for producing a toner and capable of shortening the time required for producing a toner, compared with a case where the melt viscosity of the resin particles is less than 5000 Pa·s or exceeds 20000 Pa·s.

[0041] According to <5>, a method for producing a resin particle dispersion liquid used for producing a toner and capable of shortening the time required for producing a toner is provided, compared with the case where the neutralization rate based on formula (1) is less than 30% or exceeds 80%.

[0042] According to <6>, a method for producing a toner for developing an electrostatic latent image, which can shorten the time required for production, is provided. DETAILED DESCRIPTION

[0043] Hereinafter, embodiments of the present invention will be described. These descriptions and examples are for illustrating the embodiments and do not limit the scope of the embodiments.

[0044] In the present invention, a numerical range expressed using "to" indicates a range including the numerical values ​​before and after "to" as the minimum value and the maximum value, respectively.

[0045] In the numerical ranges recorded in stages in the present invention, the upper limit or lower limit recorded in one numerical range can be replaced by the upper limit or lower limit of the numerical range recorded in other stages. And, in the numerical ranges recorded in the present invention, the upper limit or lower limit of the numerical range can be replaced by the value shown in the embodiment.

[0046] In the present invention, the term "process" includes not only independent processes but also processes that cannot be clearly distinguished from other processes as long as the purpose of the process can be achieved.

[0047] In the present invention, each component may contain a plurality of corresponding substances. When the amount of each component in the composition is mentioned in the present invention, when there are a plurality of substances corresponding to each component in the composition, unless otherwise specified, it refers to the total amount of the plurality of substances present in the composition.

[0048] In the present invention, multiple types of particles corresponding to each component may be contained. When multiple types of particles corresponding to each component are present in the composition, unless otherwise specified, the particle size of each component represents a value for a mixture of the multiple types of particles present in the composition.

[0049] In the present invention, “(meth)acrylic acid” is an expression including both acrylic acid and methacrylic acid, and “(meth)acrylate” is an expression including both acrylate and methacrylate.

[0050] In the present invention, “toner” means “toner for electrostatic latent image development”, “developer” means “electrostatic latent image developer”, and “carrier” means “carrier for electrostatic latent image development”.

[0051] In the present invention, a method of producing toner particles by aggregating and combining material particles in a dispersion medium is referred to as an EA (Emulsion Aggregation) method.

[0052] <Method for producing resin particle dispersion>

[0053] The method for producing a resin particle dispersion according to the present embodiment includes the step of emulsifying a resin to form resin particles, wherein the acid value of the resin is 5 mgKOH / g or more and 30 mgKOH / g or less, and the carboxyl group density on the surface of the resin particles is 1.0×10 -7 mol / m 2 Above and 3.0×10 -6 mol / m 2 the following.

[0054] According to the method for producing a resin particle dispersion according to the present embodiment, a resin particle dispersion is provided which is used for producing a toner and which can shorten the time required for producing the toner.

[0055] Therefore, according to the method for producing a resin particle dispersion according to the present embodiment, it is possible to reduce the environmental load in producing a toner.

[0056] If the acid value of the resin is less than 5 mgKOH / g, the electrostatic repulsion between the resin particles in the resin particle dispersion becomes small, and the resin particles are easily aggregated, so the time required for aggregation is shortened, and the controllability of the toner morphology is deteriorated. From this viewpoint, the acid value of the resin is 5 mgKOH / g or more, for example, preferably 8 mgKOH / g or more, and more preferably 10 mgKOH / g or more.

[0057] If the acid value of the resin exceeds 30 mgKOH / g, the electrostatic repulsion between the resin particles in the resin particle dispersion becomes large, making it difficult to aggregate, and the time required to produce the toner increases. From this viewpoint, the acid value of the resin is 30 mgKOH / g or less, for example, preferably 25 mgKOH / g or less, and more preferably 20 mgKOH / g or less.

[0058] The acid value of the resin is determined by using an appropriate amount of the resin as a sample and by a neutralization titration method specified in JIS K0070-1992.

[0059] If the carboxyl density on the surface of the resin particles is less than 1.0×10 -7 mol / m 2 , the electrostatic repulsion per unit surface area of ​​the resin particles in the resin particle dispersion becomes smaller, and the particles are easily aggregated, so the time required for aggregation is shortened, and the controllability of the toner morphology is deteriorated. From this point of view, the carboxyl group density on the surface of the resin particles is 1.0×10 -7 mol / m 2 or more, for example, preferably 1.3×10 -6 mol / m 2 More preferably, 1.5×10 -6 mol / m 2 above.

[0060] If the carboxyl group density on the surface of the resin particles exceeds 3.0×10 -6 mol / m 2 , the electrostatic repulsion per unit surface area of ​​the resin particles in the resin particle dispersion becomes larger, making it difficult to aggregate, and the time required to produce the toner increases. From this point of view, the carboxyl group density on the surface of the resin particles is 3.0×10 -6 mol / m 2 Below, for example, preferably 2.9×10 -6 mol / m 2 Below, more preferably 2.8×10 -6 mol / m 2 the following.

[0061] The carboxyl group density on the surface of the resin particles is determined as follows.

[0062] The resin particle dispersion was used as a sample, and the particle size distribution of the resin particles was measured using a laser diffraction particle size distribution measuring device (e.g., model: LS13-320, Beckman Coulter, Inc.), and the volume-based central particle diameter (i.e., median particle diameter) was calculated. The number of particles measured was 10,000. It was assumed that the particle diameter of all resin particles was the central particle diameter, and the density of the resin particles was assumed to be 1.1 g / cm 3 Calculate the surface area per 1g of resin particles (g / m 2 ).

[0063] The solid content of the resin particle dispersion is measured using a moisture meter (e.g., model: HB43-S, Mettler-Toledo International Inc.), and the resin particle dispersion equivalent to 20 g of the resin particles (solid content) is dispensed into a beaker. Distilled water is added to the beaker from which the resin particle dispersion was dispensed to adjust the content to 200 g.

[0064] The pH of the sample in the beaker is measured with a pH meter (e.g., model: SG2, Mettler-Toledo International Inc.), and a 0.3 mol / L nitric acid aqueous solution is added to adjust the pH to 2. Next, a 0.1 mol / L sodium hydroxide aqueous solution is added dropwise 0.1 mL at a time using an automatic titrator (e.g., model: AUT-701, DKK-TOA CORPORATION) until the pH of the sample in the beaker reaches 11.

[0065] Set the amount of 0.1 mol / L sodium hydroxide aqueous solution added as b, and calculate the pH change (d[pH] / d[b]) for each addition. Plot [pH, (d[pH] / d[b])] on an orthogonal coordinate system, and set the first maximum as the starting point of carboxyl dissociation, and the second maximum as the ending point of carboxyl dissociation. Assuming that all the sodium hydroxide aqueous solution added between these two points is consumed by the dissociation of carboxyl groups, calculate the amount of carboxyl groups per 1 g of resin particles. In addition, determine the amount of carboxyl groups per unit surface area of ​​the resin particles (mol / m 2 ), and it is set as the carboxyl group density (mol / m 2 ).

[0066] The volume average particle size of the resin particles is preferably, for example, 50 nm or more and 300 nm or less. Within this range, the aggregation of the resin particles is sufficient and the particle size distribution of the toner can be narrowed.

[0067] From the above viewpoints, the volume average particle size of the resin particles is, for example, more preferably 80 nm or more, and further preferably 100 nm or more.

[0068] From the above viewpoints, the volume average particle size of the resin particles is, for example, more preferably 250 nm or less, and further preferably 230 nm or less.

[0069] The volume particle size distribution index GSDv of the resin particles is preferably, for example, 1.18 or more and 1.99 or less. Within this range, the particle size distribution of the resin particles is narrow, and the toner particles grow to have a uniform size, and coarse powder is less likely to be generated.

[0070] From the above viewpoints, the volume particle size distribution index GSDv of the resin particles is, for example, more preferably 1.70 or less, and further preferably 1.50 or less.

[0071] The volume average particle diameter and volume particle size distribution index GSDv of the resin particles are determined as follows.

[0072] The particle size distribution of the resin particles in the resin particle dispersion is measured using a laser diffraction particle size distribution measuring device (for example, model: LS13-320, Beckman Coulter, Inc.) The number of particles measured is 10,000.

[0073] In the volume-based particle size distribution, the particle size when the particle size accumulated from the smaller diameter side to 50% is defined as the volume average particle size.

[0074] In the volume-based particle size distribution, the calculation is based on the particle size when the cumulative total from the smallest diameter reaches 16% (D16v) and the particle size when the cumulative total reaches 84% ​​(D84v) (D84v / D16v). 1 / 2 , and set this value as the volume particle size distribution index GSDv.

[0075] Resin particles at a temperature of 105°C and a shear rate of 2.6s -1 The melt viscosity is preferably, for example, 5000 Pa·s or more and 20000 Pa·s or less.

[0076] If the melt viscosity of the resin particles is 5000 Pa·s or more, the toner viscosity will not drop excessively during toner fixing and will not easily adhere to the fixing roller, resulting in less image unevenness. From this viewpoint, the melt viscosity of the resin particles is more preferably 6000 Pa·s or more, and more preferably 7000 Pa·s or more.

[0077] When the melt viscosity of the resin particles is 20,000 Pa·s or less, the toner begins to melt in a low temperature region during toner fixation, thereby improving low temperature fixability. From this viewpoint, the melt viscosity of the resin particles is preferably 19,000 Pa·s or less, and further preferably 18,000 Pa·s or less.

[0078] The melt viscosity (Pa·s) of the resin particles is measured as follows.

[0079] 1.05 g to 1.10 g of the resin particles are molded into a columnar shape and measured using a flow tester (for example, model: CFT-500, SHIMADZU CORPORATION) under the following conditions.

[0080] Mold diameter: 1mm

[0081] Mold length: 5mm

[0082] Test temperature range: 70℃~160℃

[0083] Shearing speed: 2.6s -1

[0084] Heating rate: 7℃ / min

[0085] ·Pretreatment: Vacuum the sample for 1 hour.

[0086] From the viewpoint of allowing the toner particles to contain a sufficient amount of the resin, the resin particle concentration of the resin particle dispersion is, for example, preferably 1 mass % or more, more preferably 5 mass % or more, and even more preferably 10 mass % or more.

[0087] From the viewpoint of dispersibility of the resin particles, the resin particle concentration of the resin particle dispersion is, for example, preferably 60 mass % or less, more preferably 55 mass % or less, and even more preferably 50 mass % or less.

[0088] [Resin]

[0089] The resin is a resin that becomes a binder resin of the toner particles. Examples of the resin include resins containing carboxylic acid and / or carboxylic acid ester as polymerization components. Specifically, polyester resins, styrene (meth) acrylic resins, (meth) acrylic resins, and the like are included.

[0090] The resin is preferably, for example, a polyester resin.

[0091] Examples of the polyester resin include amorphous polyester resins and crystalline polyester resins. As the polyester resin, only amorphous polyester resins, only crystalline polyester resins, or both amorphous polyester resins and crystalline polyester resins may be used.

[0092] The resin is more preferably, for example, an amorphous polyester resin.

[0093] -Amorphous polyester resin-

[0094] As the amorphous polyester resin, a commercially available product may be used, or a synthetic product may be used.

[0095] Examples of the non-crystalline polyester resin include polycondensates of polycarboxylic acids and polyols.

[0096] Examples of the polycarboxylic acid as a polymer component of the amorphous polyester resin include aliphatic dicarboxylic acids (e.g., oxalic acid, malonic acid, maleic acid, fumaric acid, citraconic acid, itaconic acid, glutaconic acid, succinic acid, alkenyl succinic acid, adipic acid, sebacic acid, etc.), alicyclic dicarboxylic acids (e.g., cyclohexane dicarboxylic acid, etc.), aromatic dicarboxylic acids (e.g., terephthalic acid, isophthalic acid, phthalic acid, naphthalene dicarboxylic acid, etc.), and anhydrides thereof or lower (e.g., carbon number 1 to 5) alkyl esters thereof. Among these, aromatic dicarboxylic acids are preferred as the polycarboxylic acid.

[0097] The polycarboxylic acid may be used together with the dicarboxylic acid in a trivalent or higher carboxylic acid having a cross-linked structure or a branched structure. Examples of the trivalent or higher carboxylic acid include trimellitic acid, pyromellitic acid, their anhydrides, or their lower (e.g., carbon number 1 to 5) alkyl esters.

[0098] The polyvalent carboxylic acid may be used alone or in combination of two or more.

[0099] Examples of the polyol as a polymerization component of the amorphous polyester resin include aliphatic diols (e.g., ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, neopentyl glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,11-undecanediol, 1,12-dodecanediol, 1,13-tridecanediol, 1,14-tetradecanediol, 1,18-octadecanediol, 1,14-docosanediol, etc.), alicyclic diols (e.g., cyclohexanediol, cyclohexanedimethanol, hydrogenated bisphenol A, etc.), and aromatic diols (e.g., ethylene oxide adducts of bisphenol A, propylene oxide adducts of bisphenol A, etc.). Among these, as the polyol, for example, aliphatic diol is preferable.

[0100] As the polyol as the polymerization component of the amorphous polyester resin, a trivalent or higher polyol having a crosslinked structure or a branched structure may be used together with a diol. Examples of the trivalent or higher polyol include glycerol, trimethylolpropane, and pentaerythritol.

[0101] The polyols may be used alone or in combination of two or more.

[0102] The glass transition temperature (Tg) of the amorphous polyester resin is, for example, preferably 50° C. or higher and 70° C. or lower, more preferably 52° C. or higher and 65° C. or lower, and further preferably 54° C. or higher and 60° C. or lower.

[0103] The glass transition temperature is determined from a DSC curve obtained by differential scanning calorimetry (DSC), more specifically, according to the "extrapolated glass transition start temperature" described in the method for determining the glass transition temperature in JIS K7121-1987 "Determination of Transition Temperature of Plastics".

[0104] The weight average molecular weight (Mw) of the amorphous polyester resin is, for example, preferably 5,000 or more and 1,000,000 or less, and more preferably 7,000 or more and 500,000 or less.

[0105] The number average molecular weight (Mn) of the amorphous polyester resin is, for example, preferably 1,500 or more and 100,000 or less, and more preferably 2,000 or more and 95,000 or less.

[0106] The molecular weight distribution Mw / Mn of the amorphous polyester resin is, for example, preferably 1.5 or more and 100 or less, and more preferably 2 or more and 60 or less.

[0107] The weight average molecular weight and the number average molecular weight are measured by gel permeation chromatography (GPC). In the molecular weight measurement by GPC, GPC HLC-8120GPC manufactured by TOSOH CORPORATION is used as a measuring device, and a column TSKgel SuperHM-M (15 cm) manufactured by TOSOH CORPORATION is used, and the solvent is THF. The weight average molecular weight and the number average molecular weight are calculated using a molecular weight calibration curve prepared from a monodisperse polystyrene standard sample based on the measurement results.

[0108] The amorphous polyester resin is obtained by a known production method. Specifically, for example, the amorphous polyester resin is obtained by setting the polymerization temperature to 180° C. to 230° C., reducing the pressure in the reaction system as necessary, and reacting while removing water and alcohol generated during condensation.

[0109] When the monomer of the raw material is insoluble or incompatible at the reaction temperature, a high boiling point solvent can be added as a cosolvent to dissolve it. In this case, the polycondensation reaction is carried out while the cosolvent is removed by distillation. When there are monomers with poor compatibility in the copolymerization reaction, for example, the monomers with poor compatibility can be condensed in advance with an acid or alcohol to be polycondensed with the monomer, and then polycondensed with the main component.

[0110] -Crystalline polyester resin-

[0111] As the crystalline polyester resin, a commercially available product may be used, or a synthetic product may be used.

[0112] Examples of the crystalline polyester resin include polycondensates of polycarboxylic acids and polyols. Since the crystalline polyester resin easily forms a crystalline structure, for example, a polycondensate of a linear aliphatic polymerizable monomer is preferably used rather than a polycondensate of a polymerizable monomer having an aromatic ring.

[0113] Examples of the polycarboxylic acid as a superposed component of the crystalline polyester resin include aliphatic dicarboxylic acids (e.g., oxalic acid, succinic acid, glutaric acid, adipic acid, suberic acid, azelaic acid, sebacic acid, 1,9-nonanedicarboxylic acid, 1,10-decanedicarboxylic acid, 1,12-dodecanedicarboxylic acid, 1,14-tetradecanedicarboxylic acid, 1,18-octadecanedicarboxylic acid, etc.), aromatic dicarboxylic acids (e.g., dibasic acids such as phthalic acid, isophthalic acid, terephthalic acid, and naphthalene-2,6-dicarboxylic acid, etc.), their anhydrides, or their lower (e.g., carbon number 1 to 5) alkyl esters.

[0114] The polycarboxylic acid may be used together with the dicarboxylic acid and a trivalent or higher carboxylic acid having a cross-linked structure or a branched structure. Examples of the trivalent carboxylic acid include aromatic carboxylic acids (e.g., 1,2,3-benzenetricarboxylic acid, 1,2,4-benzenetricarboxylic acid, 1,2,4-naphthalenetricarboxylic acid, etc.), their anhydrides, or their lower (e.g., carbon number 1 to 5) alkyl esters.

[0115] As the polycarboxylic acid, a dicarboxylic acid having a sulfonic acid group or a dicarboxylic acid having an ethylenic double bond may be used together with these dicarboxylic acids.

[0116] The polyvalent carboxylic acid may be used alone or in combination of two or more.

[0117] Examples of the polyol as a polymerization component of the crystalline polyester resin include aliphatic diols (e.g., linear aliphatic diols having a main chain portion with carbon atoms of 7 or more and 20 or less). Examples of the aliphatic diols include ethylene glycol, 1,3-propylene glycol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,11-undecanediol, 1,12-dodecanediol, 1,13-tridecanediol, 1,14-tetradecanediol, 1,18-octadecanediol, and 1,14-docosanediol.

[0118] As the polyol of the polymerization component of the crystalline polyester resin, a trivalent or higher alcohol having a cross-linked structure or a branched structure may be used together with the diol. Examples of the trivalent or higher alcohol include glycerol, trimethylolethane, trimethylolpropane, pentaerythritol, and the like.

[0119] The polyols may be used alone or in combination of two or more.

[0120] The melting temperature of the crystalline polyester resin is, for example, preferably 50° C. or higher and 100° C. or lower, more preferably 55° C. or higher and 90° C. or lower, and further preferably 60° C. or higher and 85° C. or lower.

[0121] The melting temperature is determined from a DSC curve obtained by differential scanning calorimetry (DSC) in accordance with the “melting peak temperature” described in the method for determining the melting temperature in JIS K7121-1987 “Determination of Transition Temperatures of Plastics”.

[0122] The weight average molecular weight (Mw) of the crystalline polyester resin is preferably, for example, 6,000 or more and 35,000 or less.

[0123] Similar to the amorphous polyester resin, the crystalline polyester resin can be obtained by, for example, a known production method.

[0124] -Styrene (meth) acrylic resin, (meth) acrylic resin-

[0125] Examples of the styrene (meth) acrylic resin include resins obtained by polymerizing the following styrene monomers and (meth) acrylic monomers. Examples of the (meth) acrylic resin include resins obtained by polymerizing the following (meth) acrylic monomers.

[0126] Examples of styrene monomers include styrene, α-methylstyrene, and vinylnaphthalene; alkyl-substituted styrenes such as 2-methylstyrene, 3-methylstyrene, 4-methylstyrene, 2-ethylstyrene, 3-ethylstyrene, and 4-ethylstyrene; halogen-substituted styrenes such as 2-chlorostyrene, 3-chlorostyrene, and 4-chlorostyrene; fluorine-substituted styrenes such as 4-fluorostyrene and 2,5-difluorostyrene; etc. Examples of styrene monomers include preferably styrene and α-methylstyrene. The styrene monomers may be used alone or in combination of two or more.

[0127] Examples of the (meth)acrylic acid monomer include (meth)acrylic acid, methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, n-butyl (meth)acrylate, n-pentyl (meth)acrylate, n-hexyl (meth)acrylate, n-heptyl (meth)acrylate, n-octyl (meth)acrylate, n-decyl (meth)acrylate, n-dodecyl (meth)acrylate, n-lauryl (meth)acrylate, n-tetradecyl (meth)acrylate, n-hexadecyl (meth)acrylate, n-octadecyl (meth)acrylate, isopropyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, isopentyl (meth)acrylate, neopentyl (meth)acrylate, and propyl (meth)acrylate. isohexyl (meth)acrylate, isoheptyl (meth)acrylate, isooctyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, phenyl (meth)acrylate, biphenyl (meth)acrylate, diphenylethyl (meth)acrylate, tert-butylphenyl (meth)acrylate, terphenyl (meth)acrylate, cyclohexyl (meth)acrylate, tert-butylcyclohexyl (meth)acrylate, dimethylaminoethyl (meth)acrylate, diethylaminoethyl (meth)acrylate, methoxyethyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-carboxyethyl (meth)acrylate, 2-carboxypropyl (meth)acrylate, 3-carboxypropyl (meth)acrylate, 4-carboxybutyl (meth)acrylate, (meth)acrylonitrile, (meth)acrylamide, etc. The (meth)acrylic monomer may be used alone or in combination of two or more.

[0128] As the (meth)acrylic monomer, for example, a lower alkyl (meth)acrylate is preferred. In the lower alkyl (meth)acrylate, "lower alkyl" means a group having 1 to 5 carbon atoms, and for example, a group having 2 to 4 carbon atoms is preferred, and a group having 3 or 4 carbon atoms is more preferred.

[0129] Examples of the lower alkyl (meth)acrylate include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, n-butyl (meth)acrylate, n-pentyl (meth)acrylate, isopropyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, isopentyl (meth)acrylate, and neopentyl (meth)acrylate. Among these, ethyl (meth)acrylate, n-propyl (meth)acrylate, and n-butyl (meth)acrylate are preferred, and n-butyl (meth)acrylate is particularly preferred.

[0130] The polymerization ratio of the styrene monomer to the (meth)acrylic monomer (based on mass, styrene monomer:(meth)acrylic monomer) is, for example, preferably 30:70 to 70:30, more preferably 40:60 to 60:40, and further preferably 45:55 to 55:45.

[0131] Hereinafter, “solventless emulsification” and “solvent emulsification” as embodiments of the method for producing a resin particle dispersion will be described.

[0132] In solventless emulsification or solvent emulsification, for example, by controlling the operating conditions of the apparatus and / or the amount of material used, the carboxyl group density, average particle size, particle size distribution, melt viscosity, etc. can be controlled within a preferred range.

[0133] [Solvent-free emulsification]

[0134] Solvent-free emulsification is a method of producing a resin particle dispersion without using an organic solvent.

[0135] Specifically, solvent-free emulsification includes:

[0136] A melting step of applying heat and shear force to the resin, the alkaline compound, and the surfactant and mixing them to obtain a mixture containing a molten resin; and

[0137] In the emulsification step, an aqueous medium is added while applying a shear force to the mixture to emulsify it.

[0138] For example, the solvent-free emulsification preferably uses a mixing extruder to perform the melting process and the emulsification process. The mixing extruder is a device that continuously conveys the processed material while applying heat and shear force to the processed material. Generally speaking, the structure of the mixing extruder is roughly divided into a material input port, a barrel, and a mold from upstream to downstream. A screw is provided inside the barrel. A heater for heating the inside of the barrel is provided around the barrel. The screw can be a single screw type or a twin screw type, and is preferably a twin screw type.

[0139] As the alkaline compound, for example, sodium hydroxide or potassium hydroxide is preferred. From the viewpoint of uniformity of kneading, sodium hydroxide or potassium hydroxide is preferably used in the form of an aqueous solution (ie, a sodium hydroxide aqueous solution or a potassium hydroxide aqueous solution).

[0140] The amount of the basic compound used is an amount that enables emulsification and dispersion of the mixture. Specifically, the amount of the basic compound used is preferably an amount such that the neutralization rate based on the following formula (1) is 30% or more and 80% or less.

[0141] Formula (1): Neutralization rate (%) = mb × n × 56.1 ÷ Mwb ÷ AV × 1000,

[0142] mb is the amount of basic compound used per 1g of resin (g),

[0143] n is the valence of the basic compound,

[0144] Mwb is the molecular weight of the basic compound,

[0145] AV is the acid value of the resin (mgKOH / g).

[0146] The amount of the basic compound used is preferably such that the neutralization rate based on formula (1) is 30% to 80%. Within this range, a suitable amount of components derived from the basic compound (eg, sodium) remains in the toner, and the charge amount of the toner is within a suitable range.

[0147] From the above viewpoints, the neutralization rate based on formula (1) is, for example, more preferably 33% or more, and even more preferably 35% or more.

[0148] From the above viewpoints, the neutralization rate based on formula (1) is, for example, more preferably 70% or less, and further preferably 60% or less.

[0149] The surfactant may be any of anionic surfactants, cationic surfactants, and nonionic surfactants. For example, anionic surfactants such as sulfate ester salts, sulfonates, phosphates, and soaps; cationic surfactants such as amine salts and quaternary ammonium salts; nonionic surfactants such as polyethylene glycols, alkylphenol ethylene oxide adducts, and polyols; etc. Surfactants may be used alone or in combination of two or more. Nonionic surfactants may be used together with anionic surfactants or cationic surfactants.

[0150] The amount of the surfactant used is set to an amount that allows the emulsified particles to maintain dispersion.

[0151] As the aqueous medium, for example, water with reduced ion content such as distilled water or deionized water is preferred. The aqueous medium is preferably used after adjusting the temperature to within the range of ±5°C of the internal temperature of the barrel of the kneading extruder.

[0152] In the melting step, the temperature inside the barrel of the kneading extruder is, for example, preferably 65° C. to 99° C., more preferably 75° C. to 99° C., and even more preferably 85° C. to 99° C.

[0153] In the emulsification step, the temperature inside the barrel of the kneading extruder is, for example, preferably 65° C. to 99° C., more preferably 75° C. to 99° C., and even more preferably 85° C. to 99° C.

[0154] The average supply rate of the mixture supplied from the melting step to the emulsification step is, for example, preferably 1 kg / h to 400 kg / h, more preferably 1 kg / h to 380 kg / h, and further preferably 1 kg / h to 350 kg / h.

[0155] Regarding the L / D (ratio of screw length L to screw diameter D) of the kneading extruder, for example, in the entire melting step and emulsification step, it is preferably 7 to 20, more preferably 7 to 15, and further preferably 7 to 12.

[0156] The operating conditions of the kneading extruder preferably satisfy, for example, the following formula (2).

[0157] Formula (2): 0.5≤(Pe-P0) / (F·t)≤20

[0158] Pe is the average power of the mixing extruder in the emulsification process (kW),

[0159] P0 is the idle power (kW) of the mixing extruder in the emulsification process,

[0160] F is the average supply amount (kg / s) of the mixture supplied from the melting step to the emulsification step,

[0161] t is the time required for the emulsification process (s).

[0162] Pe (average power of the kneading extruder in the emulsification step) is a value obtained by weighting the power (kW) of the screw by the time the power is maintained and averaging the results.

[0163] P0 (no-load power of the kneading extruder in the emulsification step) is the power (kW) required to rotate the screw in the absence of a material to be processed.

[0164] The operating conditions of the kneading extruder may be constant or variable within the range of formula (2).

[0165] [Solvent emulsification]

[0166] Specifically, solvent emulsification includes:

[0167] a dissolving step of mixing the resin and an organic solvent capable of dissolving the resin while applying heat to obtain a mixture in which the resin is dissolved in the organic solvent; and

[0168] In the emulsification step, after adding the basic compound to the mixture, an aqueous medium is added to disperse the mixture in the aqueous medium in the form of particles.

[0169] The solvent emulsification is preferably carried out in a stirring tank having a stirring member and a heating and cooling member. The stirring member is preferably a stirring member having a rotating shaft and stirring blades. The heating and cooling member is preferably a member that applies and / or removes heat from the wall of the stirring tank.

[0170] When the resin is a polyester resin, examples of the organic solvent that can dissolve the polyester resin include ethyl acetate, butyl acetate, propyl acetate, isopropyl acetate, acetone, methyl ethyl ketone, cyclohexanone, methyl ethyl ketone, methyl isobutyl ketone, methanol, ethanol, isopropanol, n-propanol, 2-butanol, n-butanol, diacetone alcohol, 2-ethylhexanol, and mixed solvents thereof. Among them, for example, an organic solvent or mixed solvent having a boiling point of 60° C. or higher is preferred.

[0171] As the basic compound, for example, aqueous ammonia is preferred.

[0172] The amount of the basic compound used is an amount that enables emulsification and dispersion of the mixture. Specifically, the amount of the basic compound used is preferably an amount such that the neutralization rate based on the following formula (1) is 30% or more and 80% or less.

[0173] Formula (1): Neutralization rate (%) = mb × n × 56.1 ÷ Mwb ÷ AV × 1000,

[0174] mb is the amount of basic compound used per 1g of resin (g),

[0175] n is the valence of the basic compound,

[0176] Mwb is the molecular weight of the basic compound,

[0177] AV is the acid value of the resin (mgKOH / g).

[0178] The basic compound is preferably used in an amount such that the neutralization rate based on formula (1) is 30% or more and 80% or less. Within this range, a suitable amount of components derived from the basic compound remains in the toner, and the charge amount of the toner is within a suitable range.

[0179] From the above viewpoints, the neutralization rate based on formula (1) is, for example, more preferably 33% or more, and even more preferably 35% or more.

[0180] From the above viewpoints, the neutralization rate based on formula (1) is, for example, more preferably 75% or less, and further preferably 70% or less.

[0181] The aqueous medium is preferably water with reduced ion content such as distilled water or deionized water. The aqueous medium is preferably used at a temperature adjusted to a range of 35° C. to 100° C. (for example, preferably 35° C. to 55° C.).

[0182] In the dissolving step, the temperature of the object to be treated contained in the stirring tank is, for example, preferably 50°C to 80°C, more preferably 50°C to 70°C, and further preferably 50°C to 60°C.

[0183] In the emulsification step, the temperature of the treated material contained in the stirring tank is, for example, preferably 40°C to 70°C, more preferably 40°C to 60°C, and further preferably 40°C to 50°C.

[0184] The aqueous medium in the emulsification step is preferably added dropwise, for example. The rate of dropping the aqueous medium relative to 100 parts by mass of the emulsified resin is preferably, for example, 10 parts by mass / min or more and 30 parts by mass / min or less, more preferably 13 parts by mass / min or more and 27 parts by mass / min or less, and further preferably 15 parts by mass / min or more and 25 parts by mass / min or less.

[0185] After the addition of the aqueous medium is completed, for example, preferably the inside of the stirred tank is decompressed and / or the emulsion is bubbled to remove the organic solvent. Then, in order to improve the dispersion stability of the particles, a surfactant can be added. As the surfactant, the above-mentioned anionic surfactant, cationic surfactant, and nonionic surfactant can be enumerated.

[0186] <Method for producing toner for developing electrostatic latent images>

[0187] The method for producing a toner according to the present embodiment includes a step of producing toner particles by the EA method.

[0188] In the method for producing a toner according to the present embodiment, at least resin particles obtained by the method for producing a resin particle dispersion according to the present embodiment are used as material particles. The resin particles serve as a binder resin for toner particles. Hereinafter, the resin particles obtained by the method for producing a resin particle dispersion according to the present embodiment are also referred to as "binder resin particles".

[0189] The method for producing a toner according to the present embodiment includes the step of aggregating and combining material particles including binder resin particles in a dispersion medium to obtain toner particles.

[0190] Specifically, the toner production method according to the present embodiment includes the steps of aggregating binder resin particles in a dispersion containing binder resin particles to form aggregated particles, and heating the dispersion containing the aggregated particles to fuse the aggregated particles to form toner particles.

[0191] Hereinafter, each step and material of the EA method in this embodiment will be described in detail.

[0192] [Aggregation step (first aggregating step)]

[0193] The aggregation step aggregates at least the binder resin particles in the dispersion containing at least the binder resin particles to form aggregated particles.

[0194] When the toner production method according to the present embodiment includes the second aggregation step (a step for forming a shell) described below, the aggregation step is referred to as a “first aggregation step.” The first aggregation step is a step for forming a core in a toner having a core / shell structure.

[0195] The dispersion liquid provided in the aggregation step contains at least binder resin particles. The dispersion liquid provided in the aggregation step may further contain release agent particles. The dispersion liquid provided in the aggregation step may further contain colorant particles.

[0196] The dispersion to be used in the aggregation step may be prepared by, for example, preparing a resin particle dispersion (binder resin particle dispersion) obtained by the method for producing a resin particle dispersion according to the present embodiment, a release agent particle dispersion, and a colorant particle dispersion, and mixing these particle dispersions. The order of mixing these particle dispersions is not limited.

[0197] Hereinafter, the common points between the release agent particle dispersion and the colorant particle dispersion are collectively referred to as “particle dispersion” for explanation.

[0198] An example of an embodiment of the particle dispersion is a dispersion in which a material is dispersed in a dispersion medium in the form of particles by a surfactant.

[0199] As the dispersion medium of the particle dispersion, for example, an aqueous medium is preferred. As the aqueous medium, for example, water and alcohol can be cited. As for water, for example, distilled water, deionized water and other water with reduced ion content are preferred. These aqueous media can be used alone or in combination of two or more.

[0200] The surfactant that disperses the material in the dispersion medium may be any of anionic surfactants, cationic surfactants, and nonionic surfactants. For example, anionic surfactants such as sulfate ester salts, sulfonates, phosphates, and soaps; cationic surfactants such as amine salts and quaternary ammonium salts; nonionic surfactants such as polyethylene glycols, alkylphenol ethylene oxide adducts, and polyols; etc. Surfactants may be used alone or in combination of two or more. Nonionic surfactants may be used together with anionic surfactants or cationic surfactants.

[0201] Examples of a method for dispersing the material in a dispersion medium in a particle form include known dispersion methods such as a rotary shearing homogenizer, a ball mill with a medium, a sand mill, and a DYNO-MILL.

[0202] The volume average particle size of the particles dispersed in the particle dispersion is, for example, preferably 30 nm to 300 nm, more preferably 50 nm to 250 nm, and further preferably 80 nm to 200 nm.

[0203] The volume average particle size of particles in the particle dispersion is the particle size at 50% cumulatively from the small diameter side in the particle size distribution measured by a laser diffraction particle size distribution analyzer (e.g., model: LS13-320, Beckman Coulter, Inc.) The number of particles measured is 10,000.

[0204] The content of the particles contained in the particle dispersion is, for example, preferably 5 mass % to 50 mass %, more preferably 10 mass % to 40 mass %, and further preferably 15 mass % to 30 mass %.

[0205] Hereinafter, the materials constituting the particles of each of the release agent particle dispersion and the colorant particle dispersion will be described.

[0206] -Release agent-

[0207] Examples of the release agent include hydrocarbon waxes, natural waxes such as carnauba wax, rice wax, and candelilla wax, synthetic waxes such as montan wax, or mineral / petroleum waxes, and ester waxes such as fatty acid esters and montanic acid esters. The release agent is not limited thereto.

[0208] The melting temperature of the release agent is, for example, preferably 50° C. or higher and 110° C. or lower, and more preferably 60° C. or higher and 100° C. or lower.

[0209] The melting temperature of the release agent is determined from a DSC curve obtained by differential scanning calorimetry (DSC) based on the "melting peak temperature" described in the method for determining the melting temperature in JIS K7121:1987 "Determination of Transition Temperatures of Plastics".

[0210] -Colorants-

[0211] Examples of the colorant include carbon black, chrome yellow, Hansa yellow, benzidine yellow, vat yellow, quinoline yellow, pigment yellow, permanent orange GTR, pyrazolone orange, vulcan orange, magenta, permanent red, brilliant carmine 3B, brilliant carmine 6B, Dupont Oil Red, pyrazolone red, litho red, rhodamine B lake, lake red C, pigment red, rose Bengal, aniline blue, histidine blue, copper oil blue, methylene blue chloride, phthalocyanine blue, pigment blue, phthalocyanine green, malachite green oxalate and other pigments; acridine-based, xanthene-based, azo-based, benzoquinone-based, azine-based, anthraquinone-based, thioindigo-based, dioxazine-based, thiazine-based, azomethine-based, indigo-based, phthalocyanine-based, nigrosine-based, polymethine-based, triphenylmethane-based, diphenylmethane-based, thiazole-based and other dyes; and inorganic pigments such as titanium compounds and silica.

[0212] The coloring agent may be used alone or in combination of two or more.

[0213] The colorant is not limited to a substance having absorption in the visible light region, and the colorant may be, for example, a substance having absorption in the near infrared region or a fluorescent colorant.

[0214] Examples of the colorant having absorption in the near-infrared region include ammonium salt compounds, naphthalocyanine compounds, squarylium compounds, and crotonic acid compounds.

[0215] Examples of the fluorescent colorant include the fluorescent colorants described in paragraph 0027 of JP-A-2021-127431.

[0216] The colorant may be a colorant with bright properties. Examples of the colorant with bright properties include metal powders such as aluminum, brass, bronze, nickel, stainless steel, and zinc; mica coated with titanium oxide or yellow iron oxide; a thin-flaked inorganic crystal matrix coated with barium sulfate, layered silicate, layered aluminum silicate, etc.; single-crystal plate-like titanium oxide, alkaline carbonate, bismuth oxychloride, natural guanine, thin-flaked glass powder, and thin-flaked glass powder subjected to metal vapor deposition; and the like.

[0217] The coloring agent may be used alone or in combination of two or more.

[0218] The colorant may be a surface-treated colorant as required, or may be used together with a dispersant.

[0219] In the present embodiment, the toner particles may contain a colorant or may not contain a colorant. In the present embodiment, the toner may be a toner that does not contain a colorant in the toner particles, so-called transparent toner.

[0220] Hereinafter, a dispersion obtained by mixing a plurality of types of particle dispersions will be referred to as a "mixed dispersion".

[0221] The mass ratio of the particles contained in the mixed dispersion is preferably in the following range, for example.

[0222] When the mixed dispersion contains release agent particles, the mass ratio of binder resin particles to release agent particles is, for example, preferably binder resin particles:release agent particles=100:1 to 100:40, more preferably 100:2 to 100:30, and even more preferably 100:5 to 100:20.

[0223] When the mixed dispersion contains colorant particles, the mass ratio of the binder resin particles to the colorant particles is, for example, preferably binder resin particles:colorant particles=100:1 to 100:100, more preferably 100:2 to 100:40, and even more preferably 100:5 to 100:20.

[0224] After mixing the plurality of particle dispersions, the pH of the mixed dispersion is preferably adjusted to, for example, 3 to 4. Examples of methods for adjusting the pH of the mixed dispersion include adding an acidic aqueous solution such as nitric acid, hydrochloric acid, or sulfuric acid.

[0225] The aggregation process includes, for example, the following steps:

[0226] adding a coagulant to the mixed dispersion while stirring the mixed dispersion; and

[0227] After the coagulant is added to the mixed dispersion, the mixed dispersion is heated while stirring the mixed dispersion to increase the temperature of the mixed dispersion.

[0228] Examples of the coagulant include a surfactant having a polarity opposite to that of the surfactant contained in the mixed dispersion, an inorganic metal salt, and a divalent or higher-valent metal complex. The coagulant may be used alone or in combination of two or more.

[0229] Examples of the inorganic metal salt include metal salts such as calcium chloride, calcium nitrate, barium chloride, magnesium chloride, zinc chloride, aluminum chloride, and aluminum sulfate; inorganic metal salt polymers such as polyaluminum chloride, polyaluminum hydroxide, and calcium polysulfide; and the like.

[0230] The coagulant is preferably a divalent or higher metal salt compound, more preferably a trivalent metal salt compound, and still more preferably a trivalent inorganic aluminum salt compound. Examples of the trivalent inorganic aluminum salt compound include aluminum chloride, aluminum sulfate, polyaluminum chloride, and polyaluminum hydroxide.

[0231] The amount of the coagulant added is not limited. When a trivalent metal salt compound is used as a coagulant, the amount of the trivalent metal salt compound added is, for example, preferably 0.01 parts by mass or more and 10 parts by mass or less, more preferably 0.05 parts by mass or more and 5 parts by mass or less, and further preferably 0.1 parts by mass or more and 3 parts by mass or less, relative to 100 parts by mass of the binder resin.

[0232] The temperature reached when the mixed dispersion is heated is preferably a temperature based on the glass transition temperature (Tg) of the binder resin particles, for example, not less than (Tg-30°C) and not more than (Tg°C) of the binder resin particles.

[0233] When the mixed dispersion contains a plurality of types of binder resin particles having different Tgs, the lowest temperature among the respective Tgs is defined as the Tg in the aggregation step.

[0234] [Second Aggregation Step]

[0235] The second aggregation step is a step provided for the purpose of producing a toner having a core / shell structure and is a step provided after the first aggregation step. The second aggregation step is a step for forming a shell.

[0236] The second aggregation step is a step of mixing a dispersion containing aggregated particles and a dispersion containing resin particles that serve as shells, and aggregating the resin particles that serve as shells on the surfaces of the aggregated particles to form second aggregated particles.

[0237] The dispersion containing the resin particles that serve as the shell is preferably at least one selected from the dispersions of binder resin particles that serve to form the core, more preferably a dispersion of polyester resin particles, and still more preferably an amorphous polyester resin particle dispersion.

[0238] The second coagulation step includes, for example, the following steps:

[0239] adding a dispersion containing resin particles that serve as shells to the dispersion containing the aggregated particles while stirring the dispersion containing the aggregated particles; and

[0240] The dispersion containing the aggregated particles to which the dispersion containing the resin particles serving as the shells has been added is heated while being stirred.

[0241] The temperature reached when the dispersion containing aggregated particles is heated is preferably a temperature based on the glass transition temperature (Tg) of the resin particles forming the shell, for example, (Tg-30°C) or higher and (Tg-10°C) or lower.

[0242] After the aggregated particles or second aggregated particles grow to a predetermined size and before the heating in the combining step, a chelating agent for the aggregating agent used in the aggregating step may be added to the dispersion containing the aggregated particles or second aggregated particles in order to stop the growth of the aggregated particles or second aggregated particles.

[0243] Examples of the chelating agent include hydroxycarboxylic acids such as tartaric acid, citric acid, and gluconic acid; aminocarboxylic acids such as iminodiacetic acid (IDA), nitrilotriacetic acid (NTA), and ethylenediaminetetraacetic acid (EDTA); and the like.

[0244] The amount of the chelating agent added is, for example, preferably 0.01 parts by mass or more and 5.0 parts by mass or less, and more preferably 0.1 parts by mass or more and less than 3.0 parts by mass, relative to 100 parts by mass of the binder resin particles.

[0245] After the aggregated particles or second aggregated particles grow to a predetermined size, the pH of the dispersion containing the aggregated particles or second aggregated particles may be increased for the purpose of stopping the growth of the aggregated particles or second aggregated particles before heating in the combining step.

[0246] Examples of a method for increasing the pH of the dispersion containing aggregated particles or second aggregated particles include adding at least one selected from the group consisting of an aqueous solution of an alkali metal hydroxide and an aqueous solution of an alkaline earth metal hydroxide.

[0247] The ultimate pH of the dispersion containing the aggregated particles or the second aggregated particles is preferably, for example, 8 or more and 10 or less.

[0248] [Combination process]

[0249] The agglomeration step is a step of heating the dispersion liquid containing the aggregated particles to fuse the aggregated particles into a body to form toner particles.

[0250] When the second aggregation step is provided before the combining step, the combining step is a step of heating the dispersion containing the second aggregated particles to fuse the second aggregated particles to form toner particles. By going through the second aggregation step and the combining step, toner particles with a core / shell structure can be produced.

[0251] The aspects described below are common to the aggregated particles and the second aggregated particles.

[0252] The reaching temperature of the dispersion containing the aggregated particles is preferably, for example, not less than the glass transition temperature (Tg) of the binder resin, and specifically, preferably a temperature 10° C. to 30° C. higher than the Tg of the binder resin.

[0253] When the aggregated particles contain a plurality of binder resins having different Tgs, the highest temperature among the respective Tgs is defined as the glass transition temperature in the combining step.

[0254] After the combination process is completed, the toner particles in the dispersion are subjected to a known washing process, a solid-liquid separation process, and a drying process to obtain dry toner particles. From the perspective of chargeability, the washing process is preferably performed by, for example, fully performing replacement washing with deionized water. From the perspective of productivity, the solid-liquid separation process is preferably performed by, for example, suction filtration, pressure filtration, etc. From the perspective of productivity, the drying process is preferably performed by, for example, freeze drying, airflow drying, fluidized bed drying, vibration-type fluidized bed drying, etc.

[0255] [Process of adding external additives]

[0256] The method for producing a toner according to the present embodiment preferably includes, for example, a step of adding an external additive to toner particles.

[0257] The external additive is added to the toner particles by mixing the toner particles in a dry state with the external additive. The mixing is performed, for example, by a V mixer, a Henschel mixer, a Lödige mixer, etc. Furthermore, coarse particles of the toner may be removed by using a vibration sieving machine, a wind sieving machine, etc. as needed.

[0258] Examples of external additives include inorganic particles. Examples of inorganic particles include SiO2, TiO2, Al2O3, CuO, ZnO, SnO2, CeO2, Fe2O3, MgO, BaO, CaO, K2O, Na2O, ZrO2, CaO·SiO2, K2O·(TiO2) n , Al2O3·2SiO2, CaCO3, MgCO3, BaSO4, MgSO4, etc.

[0259] For the surface of the inorganic particles as an external additive, for example, a hydrophobic treatment is preferably implemented. The hydrophobic treatment is carried out, for example, by immersing the inorganic particles in a hydrophobic treatment agent. The hydrophobic treatment agent is not particularly limited, and for example, a silane coupling agent, silicone oil, a titanate coupling agent, an aluminum coupling agent, etc. can be cited. They can be used alone or in combination of two or more.

[0260] Usually, the amount of the hydrophobizing agent is, for example, 1 part by mass or more and 10 parts by mass or less relative to 100 parts by mass of the inorganic particles.

[0261] Examples of the external additives include resin particles (polystyrene, polymethyl methacrylate, melamine resin, and other resin particles), cleaning aids (for example, metal salts of higher fatty acids such as zinc stearate, and particles of fluorine-based high molecular weight bodies), and the like.

[0262] The amount of the external additive added is, for example, preferably 0.01% by mass or more and 5% by mass or less, and more preferably 0.01% by mass or more and 2% by mass or less, relative to the mass of the toner particles.

[0263] <Toner for electrostatic latent image development>

[0264] The toner produced by the production method according to the present embodiment is preferably an externally added toner obtained by adding an external additive to toner particles, for example. The form of the external additive is as described above.

[0265] The toner particles contain at least a resin, a release agent, and a colorant.

[0266] The total content of the resin (for example, preferably a polyester resin) relative to the entire toner is, for example, preferably 40 mass % to 95 mass %, more preferably 50 mass % to 90 mass %, and further preferably 60 mass % to 85 mass %.

[0267] When the toner particles contain a crystalline polyester resin, the content of the crystalline polyester resin is, for example, preferably 3% by mass or more and 30% by mass or less, and more preferably 8% by mass or more and 20% by mass or less, based on the total binder resin.

[0268] When the toner contains a releasing agent, the content of the releasing agent is, for example, preferably 1 mass % or more and 20 mass % or less, and more preferably 5 mass % or more and 15 mass % or less, based on the entire toner.

[0269] When the toner contains a colorant, the content of the colorant is, for example, preferably 1 mass % or more and 30 mass % or less, and more preferably 3 mass % or more and 15 mass % or less, based on the entire toner.

[0270] The volume average particle size of the toner is, for example, preferably 2 μm or more and 10 μm or less, and more preferably 4 μm or more and 8 μm or less. The method for measuring the volume average particle size of the toner is as follows.

[0271] The particle size distribution of the toner is measured using Coulter Multisizer II (manufactured by Beckman Coulter, Inc.) and ISOTON-II (manufactured by Beckman Coulter, Inc.) for the electrolyte. During the measurement, as a dispersant, add 0.5 mg or more and 50 mg or less of the measurement sample to 2 ml of a 5% aqueous solution of a surfactant (e.g., preferably sodium alkylbenzene sulfonate). Add it to an electrolyte of 100 ml or more and 150 ml or less. The electrolyte in which the sample is suspended is dispersed for 1 minute using an ultrasonic disperser, and the particle size distribution of particles with a particle size range of 2 μm or more and 60 μm or less is measured using a Coulter Multisizer II with a hole of 100 μm in diameter. The number of particles measured is 50,000. The particle size distribution is plotted from the smaller diameter side, and the particle size when accumulated to 50% is set as the volume average particle size D50v.

[0272] The average circularity of the toner is, for example, preferably 0.94 or more and 1.00 or less, and more preferably 0.95 or more and 0.98 or less.

[0273] The average circularity of the toner is (the circumference of a circle having the same area as the particle projection image) / (the circumference of the particle projection image) and is determined by measuring 3,500 particles using a flow particle image analyzer (FPIA-3000 manufactured by Sysmex Corporation).

[0274] <Developer>

[0275] The toner produced by the production method according to the present embodiment may be used as a single-component developer, or may be mixed with a carrier and used as a two-component developer.

[0276] The carrier is not particularly limited, and known carriers may be used. Examples of the carrier include a coated carrier in which the surface of a core material composed of magnetic powder is coated with a resin; a magnetic powder dispersed carrier in which magnetic powder is dispersed in a matrix resin; a resin impregnated carrier in which porous magnetic powder is impregnated with a resin; and the like.

[0277] The magnetic powder dispersed carrier or the resin impregnated carrier may be a carrier having constituent particles of the carrier as a core material and the surface of the core material coated with a resin.

[0278] Examples of the magnetic powder include magnetic metals such as iron, nickel, and cobalt; magnetic oxides such as ferrite and magnetite; and the like.

[0279] As the coating resin and the base resin, for example, polyethylene, polypropylene, polystyrene, polyvinyl acetate, polyvinyl alcohol, polyvinyl butyral, polyvinyl chloride, polyvinyl ether, polyvinyl ketone, vinyl chloride-vinyl acetate copolymer, acrylate copolymer, styrene-acrylate copolymer, resin with cycloalkyl group, acrylate copolymer with cycloalkyl group, straight-chain silicone resin or its modified product containing organic siloxane bond, fluororesin, polyester, polycarbonate, phenolic resin, epoxy resin, etc. are mentioned. For example, acrylate copolymer, styrene-acrylate copolymer, resin with cycloalkyl group, acrylate copolymer with cycloalkyl group are preferred. The coating resin and the base resin may contain other additives such as conductive particles. As conductive particles, metals such as gold, silver, copper, carbon black, titanium oxide, zinc oxide, tin oxide, barium sulfate, aluminum borate, potassium titanate and other particles can be mentioned.

[0280] In order to coat the surface of the core material with resin, a coating layer formed by dissolving the coating resin and various additives (used as required) in a suitable solvent can be enumerated to coat with a solution, etc. As the solvent, there is no particular limitation, as long as the type of the resin used and coating suitability are considered to select.

[0281] Specific resin coating methods include an immersion method in which the core material is immersed in a coating layer forming solution; a spraying method in which the coating layer forming solution is sprayed on the surface of the core material; a fluidized bed method in which the coating layer forming solution is sprayed while the core material is suspended by flowing air; a kneading coating method in which the core material of the carrier and the coating layer forming solution are mixed in a kneading coater and then the solvent is removed; and the like.

[0282] The mixing ratio (mass ratio) of the toner and the carrier in the two-component developer is, for example, preferably toner:carrier=1:100 to 30:100, and more preferably 3:100 to 20:100.

[0283] Example

[0284] Hereinafter, embodiments of the present invention will be described in detail based on examples, but embodiments of the present invention are not limited to these examples.

[0285] In the following description, "parts" and "%" are based on mass unless otherwise specified.

[0286] In the following description, unless otherwise specified, synthesis, production, treatment, measurement, etc. were performed at room temperature (25° C.±3° C.).

[0287] <Production of amorphous polyester resin>

[0288] [Preparation of amorphous polyester resin (A)]

[0289] The following materials were prepared.

[0290] Terephthalic acid: 30 mol parts

[0291] Fumaric acid: 70 mol parts

[0292] Bisphenol A ethylene oxide adduct: 5 mol parts

[0293] Bisphenol A propylene oxide adduct: 95 mol parts

[0294] The above materials were placed in a flask equipped with a stirring device, a nitrogen inlet pipe, a temperature sensor and a distillation tower, and the temperature of the reaction liquid was raised to 220°C over 1 hour, and 1 part of tetraethoxytitanium was added to 100 parts of the above materials. The temperature of the reaction liquid was raised to 230°C over 30 minutes while distilling off the generated water, and the dehydration condensation reaction was continued for 1 hour while the temperature of the reaction liquid was maintained at 230°C. Then, the temperature of the reactant was cooled to room temperature. In this way, an amorphous polyester resin (A) with an acid value of 13.0 mgKOH / g, a number average molecular weight of 6000, and a glass transition temperature of 60°C was obtained.

[0295] [Preparation of amorphous styrene acrylic resin (B)]

[0296] The following materials were prepared.

[0297] Styrene: 77 molar parts

[0298] n-Butyl acrylate: 23 mol parts

[0299] 1,10-Decanediol diacrylate: 0.4 mol parts

[0300] · Dodecanethiol: 0.7 mol parts

[0301] The above materials were placed in a flask equipped with a stirring device, a nitrogen inlet pipe, a temperature sensor and a distillation tower, and the temperature of the reaction solution was raised to 220°C over 1 hour, and 1 part of tetraethoxytitanium was added to 100 parts of the above materials. The temperature of the reaction solution was raised to 230°C over 30 minutes while distilling off the generated water, and the dehydration condensation reaction was continued for 1 hour while the temperature of the reaction solution was maintained at 230°C. Then, the temperature of the reactant was cooled to room temperature. In this way, an amorphous styrene acrylic resin (B) with an acid value of 13.0 mgKOH / g, a number average molecular weight of 6000, and a glass transition temperature of 60°C was obtained.

[0302] [Preparation of amorphous polyester resin (C)]

[0303] The following materials were prepared.

[0304] Terephthalic acid: 19 parts by mole

[0305] Fumaric acid: 59 mol parts

[0306] Bisphenol A ethylene oxide adduct: 16 molar parts

[0307] Bisphenol A propylene oxide adduct: 106 molar parts

[0308] The above materials were placed in a flask equipped with a stirring device, a nitrogen inlet pipe, a temperature sensor and a distillation tower, and the temperature of the reaction liquid was raised to 220°C over 1 hour, and 1 part of tetraethoxytitanium was added to 100 parts of the above materials. The temperature of the reaction liquid was raised to 230°C over 30 minutes while distilling off the generated water, and the dehydration condensation reaction was continued for 1 hour while the temperature of the reaction liquid was maintained at 230°C. Then, the temperature of the reactant was cooled to room temperature. In this way, an amorphous polyester resin (C) with an acid value of 5.5 mgKOH / g, a number average molecular weight of 8000, and a glass transition temperature of 66°C was obtained.

[0309] [Preparation of amorphous polyester resin (D)]

[0310] The following materials were prepared.

[0311] Terephthalic acid: 20 mol parts

[0312] Fumaric acid: 60 mol parts

[0313] Bisphenol A ethylene oxide adduct: 15 mol parts

[0314] Bisphenol A propylene oxide adduct: 105 mol parts

[0315] The above materials were placed in a flask equipped with a stirring device, a nitrogen inlet pipe, a temperature sensor and a distillation tower, and the temperature of the reaction liquid was raised to 220°C over 1 hour, and 1 part of tetraethoxytitanium was added to 100 parts of the above materials. The temperature of the reaction liquid was raised to 230°C over 30 minutes while distilling off the generated water, and the dehydration condensation reaction was continued for 1 hour while the temperature of the reaction liquid was maintained at 230°C. Then, the temperature of the reactant was cooled to room temperature. In this way, an amorphous polyester resin (D) with an acid value of 6.0 mgKOH / g, a number average molecular weight of 7500, and a glass transition temperature of 65°C was obtained.

[0316] [Preparation of amorphous polyester resin (E)]

[0317] The following materials were prepared.

[0318] Terephthalic acid: 40 mol parts

[0319] Fumaric acid: 80 mol parts

[0320] Bisphenol A ethylene oxide adduct: 5 mol parts

[0321] Bisphenol A propylene oxide adduct: 75 mol parts

[0322] The above materials were placed in a flask equipped with a stirring device, a nitrogen inlet pipe, a temperature sensor and a distillation tower, and the temperature of the reaction liquid was raised to 220°C over 1 hour, and 1 part of tetraethoxytitanium was added to 100 parts of the above materials. The temperature of the reaction liquid was raised to 230°C over 30 minutes while distilling off the generated water, and the dehydration condensation reaction was continued for 1 hour while the temperature of the reaction liquid was maintained at 230°C. Then, the temperature of the reactant was cooled to room temperature. In this way, an amorphous polyester resin (E) with an acid value of 20.0 mgKOH / g, a number average molecular weight of 4500, and a glass transition temperature of 50°C was obtained.

[0323] [Preparation of amorphous polyester resin (F)]

[0324] The following materials were prepared.

[0325] Terephthalic acid: 45 mol parts

[0326] Fumaric acid: 85 mol parts

[0327] Bisphenol A ethylene oxide adduct: 5 mol parts

[0328] Bisphenol A propylene oxide adduct: 65 mol parts

[0329] The above materials were placed in a flask equipped with a stirring device, a nitrogen inlet pipe, a temperature sensor and a distillation tower, and the temperature of the reaction liquid was raised to 220°C over 1 hour, and 1 part of tetraethoxytitanium was added to 100 parts of the above materials. The temperature of the reaction liquid was raised to 230°C over 30 minutes while distilling off the generated water, and the dehydration condensation reaction was continued for 1 hour while the temperature of the reaction liquid was maintained at 230°C. Then, the temperature of the reactant was cooled to room temperature. In this way, an amorphous polyester resin (F) with an acid value of 25.0 mgKOH / g, a number average molecular weight of 3500, and a glass transition temperature of 46°C was obtained.

[0330] [Preparation of amorphous polyester resin (G)]

[0331] The following materials were prepared.

[0332] Terephthalic acid: 15 mol parts

[0333] Fumaric acid: 55 mol parts

[0334] Bisphenol A ethylene oxide adduct: 20 mol parts

[0335] Bisphenol A propylene oxide adduct: 110 mol parts

[0336] The above materials were placed in a flask equipped with a stirring device, a nitrogen inlet pipe, a temperature sensor and a distillation tower, and the temperature of the reaction liquid was raised to 220°C over 1 hour, and 1 part of tetraethoxytitanium was added to 100 parts of the above materials. The temperature of the reaction liquid was raised to 230°C over 30 minutes while distilling off the generated water, and the dehydration condensation reaction was continued for 1 hour while the temperature of the reaction liquid was maintained at 230°C. Then, the temperature of the reactant was cooled to room temperature. In this way, an amorphous polyester resin (G) with an acid value of 5.0 mgKOH / g, a number average molecular weight of 9000, and a glass transition temperature of 68°C was obtained.

[0337] [Preparation of amorphous polyester resin (H)]

[0338] The following materials were prepared.

[0339] Terephthalic acid: 50 mol parts

[0340] Fumaric acid: 90 mol parts

[0341] Bisphenol A ethylene oxide adduct: 5 mol parts

[0342] Bisphenol A propylene oxide adduct: 55 mol parts

[0343] The above materials were placed in a flask equipped with a stirring device, a nitrogen inlet pipe, a temperature sensor and a distillation tower, and the temperature of the reaction liquid was raised to 220°C over 1 hour, and 1 part of tetraethoxytitanium was added to 100 parts of the above materials. The temperature of the reaction liquid was raised to 230°C over 30 minutes while distilling off the generated water, and the dehydration condensation reaction was continued for 1 hour while the temperature of the reaction liquid was maintained at 230°C. Then, the temperature of the reactant was cooled to room temperature. In this way, an amorphous polyester resin (H) having an acid value of 30.0 mgKOH / g, a number average molecular weight of 3000, and a glass transition temperature of 45°C was obtained.

[0344] [Preparation of amorphous polyester resin (I)]

[0345] The following materials were prepared.

[0346] Terephthalic acid: 10 parts by mole

[0347] Fumaric acid: 90 mol parts

[0348] Bisphenol A ethylene oxide adduct: 5 mol parts

[0349] Bisphenol A propylene oxide adduct: 60 mol parts

[0350] The above materials were placed in a flask equipped with a stirring device, a nitrogen inlet pipe, a temperature sensor and a distillation tower, and the temperature of the reaction liquid was raised to 220°C over 1 hour, and 1 part of tetraethoxytitanium was added to 100 parts of the above materials. The temperature of the reaction liquid was raised to 230°C over 30 minutes while distilling off the generated water, and the dehydration condensation reaction was continued for 1 hour while the temperature of the reaction liquid was maintained at 230°C. Then, the temperature of the reactant was cooled to room temperature. In this way, an amorphous polyester resin (I) with an acid value of 4.0 mgKOH / g, a number average molecular weight of 9200, and a glass transition temperature of 70°C was obtained.

[0351] [Preparation of amorphous polyester resin (J)]

[0352] The following materials were prepared.

[0353] Terephthalic acid: 55 mol parts

[0354] Fumaric acid: 90 mol parts

[0355] Bisphenol A ethylene oxide adduct: 5 mol parts

[0356] Bisphenol A propylene oxide adduct: 60 mol parts

[0357] The above materials were placed in a flask equipped with a stirring device, a nitrogen inlet pipe, a temperature sensor and a distillation tower, and the temperature of the reaction liquid was raised to 220°C over 1 hour, and 1 part of tetraethoxytitanium was added to 100 parts of the above materials. The temperature of the reaction liquid was raised to 230°C over 30 minutes while distilling off the generated water, and the dehydration condensation reaction was continued for 1 hour while the temperature of the reaction liquid was maintained at 230°C. Then, the temperature of the reactant was cooled to room temperature. In this way, an amorphous polyester resin (J) with an acid value of 32.0 mgKOH / g, a number average molecular weight of 3000, and a glass transition temperature of 43°C was obtained.

[0358] <Preparation of resin particle dispersion>

[0359] [Preparation of Resin Particle Dispersion (P1)]

[0360] The following materials were prepared.

[0361] Amorphous polyester resin (A): 200 parts

[0362] Alkaline compound: 25% sodium hydroxide aqueous solution: 0.4 parts

[0363] Surfactant: 48.5% sodium dodecyl diphenyl ether disulfonate aqueous solution (trade name: ELEMINOL MON-7, SANYO CHEMICAL INDUSTRIES, LTD.): 4.1 parts

[0364] Deionized water (1): 150 parts of deionized water at 90°C

[0365] Deionized water (2): 150 parts of deionized water at 90°C

[0366] Deionized water (3): 150 parts of deionized water at 90°C

[0367] A twin-screw kneading extruder (model: TEM26SS, Toshiba Machine Co., Ltd.) was prepared. The barrel of the twin-screw kneading extruder used in this example was formed by connecting a plurality of barrel blocks.

[0368] - Melting process -

[0369] The barrel temperature of the twin-screw kneading extruder was set to 90°C and the screw speed was set to 400 rpm. Amorphous polyester resin (A) and 25% sodium hydroxide aqueous solution were added to the raw material inlet of the twin-screw kneading extruder, and the operation of the twin-screw kneading extruder was started. A surfactant was added from the barrel of the fourth block, and kneading and stirring were performed to melt the resin to prepare a mixture.

[0370] -Emulsification process-

[0371] While operating the twin-screw kneading extruder so that the average feed rate of the mixture is 12 kg / h, deionized water (1) is added from the barrel of the fifth block, deionized water (2) is added from the barrel of the seventh block, and deionized water (3) is added from the barrel of the ninth block to emulsify the mixture to obtain a resin particle dispersion (P1). The solid content concentration of the resin particle dispersion (P1) is 30%.

[0372] The particle size distribution of the particles in the resin particle dispersion (P1) was measured using a laser diffraction particle size distribution measuring instrument (model: LS13-320, Beckman Coulter, Inc.) The volume average particle size of the particles in the resin particle dispersion (P1) was 180 nm.

[0373] [Preparation of Resin Particle Dispersion (P2)]

[0374] A resin particle dispersion (P2) was prepared in the same manner as in the preparation of the resin particle dispersion (P1), except that the amorphous polyester resin (A) was replaced with the amorphous styrene acrylic resin (B).

[0375] [Preparation of Resin Particle Dispersions (P3) to (P7) and (P15) to (P18)]

[0376] The same method as in the preparation of the resin particle dispersion (P1) was carried out, but the type of the amorphous polyester resin was changed as described in Table 1, to prepare respective resin particle dispersions.

[0377] [Preparation of Resin Particle Dispersions (P8) to (P13)]

[0378] Resin particle dispersions were prepared in the same manner as in the preparation of the resin particle dispersion (P1), except that the particle size of the resin particles was controlled by the operating speed of the twin-screw kneading extruder.

[0379] [Preparation of Resin Particle Dispersion (P14)]

[0380] The following materials were prepared.

[0381] Organic solvent (1): ethyl acetate: 60 parts

[0382] Organic solvent (2): Isopropyl alcohol: 24 parts

[0383] Amorphous polyester resin (A): 100 parts

[0384] Alkaline compound: 10% ammonia water: 3.3 parts

[0385] Deionized water (4): 500 parts of deionized water at 40°C

[0386] -Dissolution process-

[0387] An organic solvent (1) and an organic solvent (2) are placed in a stirring tank equipped with a stirrer, a capacitor, a heating device and a thermometer to prepare a mixed solvent. While the temperature in the stirring tank is maintained at 50°C and stirred, an amorphous polyester resin (A) is placed and stirred for 30 minutes to dissolve the resin in the organic solvent.

[0388] -Emulsification process-

[0389] While maintaining the temperature in the stirring tank and stirring continuously, 10% ammonia water is added, and then deionized water (4) is added dropwise to emulsify the contents. The heating of the stirring tank is stopped, and after the temperature of the emulsion is lowered to room temperature, the stirring tank is depressurized to remove the organic solvent from the emulsion. The emulsion is passed through a sieve to obtain a resin particle dispersion (P14). The solid content concentration of the resin particle dispersion (P14) is 30%. The volume average particle size of the particles in the resin particle dispersion (P14) is 180nm.

[0390] <Preparation of Release Agent Particle Dispersion (1)>

[0391] The following materials were prepared.

[0392] Paraffin (HNP-9, NIPPON SEIRO CO., LTD.): 100 parts

[0393] Deionized water: 350 parts

[0394] Anionic surfactant (trade name: NEOGEN RK, manufactured by DKS Co. Ltd., 20% aqueous solution): 1 part

[0395] The above materials were mixed and heated to 100°C, dispersed using a homogenizer (ULTRA TURRAX T50, IKA), and then dispersed using a pressure-dispensing homogenizer (Manton-Gaulin high-pressure homogenizer, Gaulin). When the volume average particle size reached 200 nm, the particles were recovered to obtain a release agent particle dispersion (1) having a solid content concentration of 20%.

[0396] The following is an example of manufacturing a toner and a developer. In the following examples and comparative examples, the target particle size of the toner particles is 5.0 μm. To achieve this particle size, the time required for the first aggregation step and the time required for the combination step in the EA method are adjusted.

[0397] <Example 1>

[0398] [Manufacturing of Toner Particles]

[0399] The following materials were prepared.

[0400] Deionized water: 550 parts

[0401] Resin particle dispersion (P1): 400 parts

[0402] Release agent particle dispersion (1): 80 parts

[0403] Anionic surfactant (trade name: NEOGEN RK, manufactured by DKS Co. Ltd., 20% aqueous solution): 10 parts

[0404] -First Coagulation Step-

[0405] The above materials were placed in a round stainless steel flask, 0.1N nitric acid was added and the pH was adjusted to 3.5, and 30 parts of a nitric acid aqueous solution with a polyaluminum chloride concentration of 10% was added. The liquid temperature was adjusted to 30°C using an oil bath, and a homogenizer (trade name: ULTRA TURRAX T50, IKA) was used for dispersion treatment. Then, the liquid temperature was raised to 45°C and maintained for 160 minutes to form the first aggregated particles.

[0406] -Second Coagulation Step-

[0407] While the liquid temperature of the dispersion liquid containing the first aggregated particles was maintained at 45° C., 120 parts of the resin particle dispersion liquid (P1) was added and maintained for 10 minutes to form second aggregated particles.

[0408] -Combination process-

[0409] A 0.1 N sodium hydroxide aqueous solution was added to the dispersion containing the second aggregated particles to adjust the pH to 8.5, and the liquid temperature was raised to 84°C and maintained for 80 minutes. Then, the dispersion was cooled to 20°C at a rate of 20°C / min, and the solid content was filtered out, washed with deionized water, and dried. The dried product was sieved to obtain toner particles (1). The volume average particle size of the toner particles (1) was 5.0 μm.

[0410] [Manufacturing of external toner]

[0411] 1.5 parts of hydrophobic silica particles (product code: RY50, NIPPONAEROSIL CO., LTD.) and 1.0 part of hydrophobic titanium oxide (product code: T805, NIPPON AEROSIL CO., LTD.) were added to 100 parts of the toner particles (1), and mixed at 10000 rpm for 30 seconds using a sample mill. Then, the mixture was sieved with a vibration sieve having an aperture of 45 μm to obtain an external toner.

[0412] [Manufacturing of developer]

[0413] 8 parts of the external toner and 92 parts of the following carrier (1) were placed in a V mixer and stirred for 20 minutes, and then sieved with a sieve having an aperture of 212 μm to obtain a developer.

[0414] -Manufacturing of carrier (1)-

[0415] 14 parts of toluene, 5 parts of cyclohexyl methacrylate-monoethylaminoethyl methacrylate copolymer (mass ratio 95:5, weight average molecular weight 60000) and 0.2 parts of carbon black (product code: VXC-72, Cabot Corporation) were placed in a sand mill and dispersed to prepare a dispersion. The dispersion and 100 parts of ferrite particles (average particle size 35 μm) were placed in a vacuum degassing kneader and dried under reduced pressure while stirring to obtain a carrier (1).

[0416] <Example 2 to Example 13, Comparative Example 1 to Comparative Example 5>

[0417] The same procedure as in Example 1 was carried out except that the type of the resin particle dispersion was changed as shown in Table 1, and toner particles, an external toner, and a developer were prepared.

[0418] <Performance Evaluation>

[0419] [Degree of reduction in manufacturing time]

[0420] The total time of the first aggregation step and the combining step was classified as follows: If the time is too short, the controllability of the toner form is deteriorated, so the case where the time is 150 minutes or less is evaluated as C. The results are shown in Table 1.

[0421] A: The total time is more than 150 minutes and less than 250 minutes

[0422] A-: Total time is more than 250 minutes and less than 275 minutes

[0423] B: Total time is more than 275 minutes and less than 300 minutes

[0424] B-: Total time is more than 300 minutes and less than 325 minutes

[0425] C: Total time is more than 325 minutes and less than 150 minutes

[0426] [Charge amount of developer]

[0427] The developer was placed in an environment of 23°C and 50% relative humidity for 24 hours and temperature and humidity were adjusted. Under the same environment, 7.5 g of the developer was placed in a Turbula mixer and stirred, and the charge (μC / g) of the developer after stirring for 10 seconds was measured using a blow-off charge measuring device. The results are shown in Table 1.

[0428]

[0429] The method for producing a resin particle dispersion and the method for producing a toner for developing an electrostatic latent image of the present invention include the following aspects. (1)

[0431] A method for producing a resin particle dispersion, comprising the step of emulsifying a resin to form resin particles, wherein:

[0432] The acid value of the resin is 5 mgKOH / g or more and 30 mgKOH / g or less,

[0433] The carboxyl density on the surface of the resin particles is 1.0×10 -7 mol / m 2 Above and 3.0×10 -6 mol / m 2 the following. (2)

[0435] The method for producing a resin particle dispersion according to (1), wherein

[0436] The resin includes a polyester resin. (3)

[0438] The method for producing a resin particle dispersion according to (1) or (2), wherein:

[0439] The resin particles have a volume average particle diameter of 50 nm or more and 300 nm or less, and a volume particle size distribution index GSDv of 1.18 or more and 1.99 or less. (4)

[0441] The method for producing a resin particle dispersion according to any one of (1) to (3), wherein

[0442] At a temperature of 105°C and a shear rate of 2.6s -1 The melt viscosity of the resin particles is 5000 Pa·s or more and 20000 Pa·s or less. (5)

[0444] The method for producing a resin particle dispersion according to any one of (1) to (4), comprising the steps of: using a basic compound in an amount such that a neutralization rate based on the following formula (1) is 30% or more and 80% or less,

[0445] Formula (1): Neutralization rate (%) = mb × n × 56.1 ÷ Mwb ÷ AV × 1000,

[0446] mb is the usage amount (g) of the basic compound per 1g of the resin,

[0447] n is the valence of the basic compound,

[0448] Mwb is the molecular weight of the basic compound,

[0449] AV is the acid value of the resin (mgKOH / g). (6)

[0451] A method for producing a toner for electrostatic latent image development comprises the following steps:

[0452] A resin particle dispersion obtained by the method for producing a resin particle dispersion according to any one of (1) to (5);

[0453] aggregating the resin particles contained in the resin particle dispersion to form aggregated particles in a dispersion containing the resin particles; and

[0454] The dispersion liquid containing the aggregated particles is heated to fuse the aggregated particles into a body, thereby forming toner particles.

[0455] According to (1) or (2), the acid value of the resin is less than 5 mgKOH / g or exceeds 30 mgKOH / g, or the carboxyl group density on the surface of the resin particles is less than 1.0×10 -7 mol / m 2 or more than 3.0×10 -6 mol / m 2 Provided is a method for producing a resin particle dispersion liquid which is used for producing a toner and which can shorten the time required for producing a toner, as compared with the case of the present invention.

[0456] According to (3), a method for manufacturing a resin particle dispersion for use in manufacturing a toner is provided, which can shorten the time required for manufacturing a toner, compared with the case where the volume average particle size of the resin particles is less than 50 nm or exceeds 300 nm, or the volume particle size distribution index GSDv of the resin particles is less than 1.18 or exceeds 1.99.

[0457] According to (4), at a temperature of 105°C and a shear rate of 2.6 s -1 Provided is a method for producing a resin particle dispersion liquid for producing a toner and capable of shortening the time required for producing a toner, compared with a case where the melt viscosity of the resin particles is less than 5000 Pa·s or exceeds 20000 Pa·s.

[0458] According to (5), a method for producing a resin particle dispersion for producing a toner is provided, which can shorten the time required for producing the toner, compared with the case where the neutralization rate based on formula (1) is less than 30% or more than 80%.

[0459] According to (6), a method for producing a toner for developing an electrostatic latent image, which can shorten the time required for production, is provided.

[0460] The above-mentioned embodiments of the present invention are provided for the purpose of illustration and description. In addition, the embodiments of the present invention do not fully and exhaustively include the present invention, and do not limit the present invention to the disclosed methods. Obviously, various modifications and changes are self-evident to those skilled in the art to which the present invention belongs. The present embodiment is selected and described in order to most easily understand the principles of the present invention and its application. Thus, other technicians in the art can understand the present invention through various variations optimized for specific uses assumed to be various embodiments. The scope of the present invention is defined by the above claims and their equivalents.

Claims

1. A method for producing a resin particle dispersion, comprising the step of emulsifying a resin to form resin particles, wherein: The acid value of the resin is 5 mgKOH / g or more and 30 mgKOH / g or less, The carboxyl density on the surface of the resin particles is 1.0×10 -7 mol / m 2 Above and 3.0×10 -6 mol / m 2 the following.

2. The method for producing a resin particle dispersion according to claim 1, wherein The resin includes a polyester resin.

3. The method for producing a resin particle dispersion according to claim 1 or 2, wherein: The resin particles have a volume average particle diameter of 50 nm or more and 300 nm or less, and a volume particle size distribution index GSDv of 1.18 or more and 1.99 or less.

4. The method for producing a resin particle dispersion according to any one of claims 1 to 3, wherein At a temperature of 105°C and a shear rate of 2.6s -1 The melt viscosity of the resin particles is 5000 Pa·s or more and 20000 Pa·s or less.

5. The method for producing a resin particle dispersion according to any one of claims 1 to 4, comprising the steps of: using a basic compound in an amount such that a neutralization rate based on the following formula (1) becomes 30% or more and 80% or less, Formula (1): Neutralization rate (%) = mb × n × 56.1 ÷ Mwb ÷ AV × 1000, mb is the usage amount (g) of the basic compound per 1g of the resin, n is the valence of the basic compound, Mwb is the molecular weight of the basic compound, AV is the acid value of the resin (mgKOH / g).

6. A method for producing a toner for electrostatic latent image development, comprising the following steps: A resin particle dispersion obtained by the method for producing a resin particle dispersion according to any one of claims 1 to 5; aggregating the resin particles contained in the resin particle dispersion to form aggregated particles in a dispersion containing the resin particles; and The dispersion liquid containing the aggregated particles is heated to fuse the aggregated particles into a body, thereby forming toner particles.